Bank attractiveness evaluation method based on soft computing in the analytic hierarchy process - Dabahian, Davyd; Godlevskyi, Mykhailo (My University, 2018)
The article offers a methodology for solving the problem of allocating investments to optimize the work of the bank. For this, a hierarchy of criteria is formed based on the use of expert information. After that, a formalized presentation of the problem is given: how to allocate the amount of investment according to the criteria in the optimal way. Due to the fact that the evaluation criteria are contradictory, a utility function is built on the basis of the mathematical apparatus of fuzzy sets to solve the problem. The result of the work is a mathematical model for solving the problem of distribution of investments.
Keywords: analytic hierarchy process; soft computing; bank evaluation